Age‐Based Life Histories of Epinephelus fasciatus , Lethrinus obsoletus , and Siganus punctatus From the Commercial Fishery of Guam, Micronesia - Brett M. Taylor; Cassandra Pardee; John Wiley; Leilani Sablan (New Zealand Journal of Marine and Freshwater Research, 2026)
Age‐based life‐history information provides a foundation for evaluating population dynamics and vulnerability of coral reef fishes, yet many commercially important species from the tropical western Pacific remain poorly characterized. In this study, we examined the age, growth, and reproductive life histories of three reef‐associated species harvested in Guam's commercial fishery: the blacktip grouper Epinephelus fasciatus , the orangestripe emperor Lethrinus obsoletus , and the goldspotted spinefoot rabbitfish Siganus punctatus . All specimens were obtained through the NOAA‐funded commercial fisheries biosampling program, with a total of 120 L. obsoletus , 110 E. fasciatus , and 97 S. punctatus sampled from local markets. Age estimates were derived from sagittal otoliths, and reproductive parameters were assessed through gonadal examination. Despite differences in trophic guilds, all three species reached similar asymptotic fork lengths (26.1, 26.7, and 24.7 cm, respectively), and females of all species matured at approximately 20 cm fork length. Maximum observed ages were 13 years for E. fasciatus and L. obsoletus and 10 years for S. punctatus . Growth trajectories differed markedly among species, with the two carnivorous taxa exhibiting slower growth rates relative to the herbivorous rabbitfish, resulting in a younger age at maturation for S. punctatus . These results highlight both shared and contrasting life‐history traits among cooccurring reef fishes with similar body sizes but contrasting trophic guilds. Over the past 15 years, age‐based research on coral reef fisheries in the southern Mariana Islands has expanded rapidly, and these species fill critical gaps within an increasingly comprehensive life‐history framework that underpins biologically informed assessments of stock status and vulnerability.